Small-Molecule Protein-Protein Interaction Inhibitor of Oncogenic Rho Signaling. Issue 9 (22nd September 2016) - Diviani, Dario; Raimondi, Francesco; Del Vescovo, Cosmo D.; Dreyer, Elisa; Reggi, Erica; Osman, Halima; Ruggieri, Lucia; Gonano, Cynthia; Cavin, Sabrina; Box, Clare L.; Lenoir, Marc; Overduin, Michael; et al.
Summary: Uncontrolled activation of Rho signaling by RhoGEFs, in particular AKAP13 (Lbc) and its close homologs, is implicated in a number of human tumors with poor prognosis and resistance to therapy. Structure predictions and alanine scanning mutagenesis of Lbc identified a circumscribed hot region for RhoA recognition and activation. Virtual screening targeting that region led to the discovery of an inhibitor of Lbc-RhoA interaction inside cells. By interacting with the DH domain, the compound inhibits the catalytic activity of Lbc, halts cellular responses to activation of oncogenic Lbc pathways, and reverses a number of prostate cancer cell phenotypes such as proliferation, migration, and invasiveness. This study provides insights into the structural determinants of Lbc-RhoA recognition. This is a successful example of structure-based discovery of a small protein-protein interaction inhibitor able to halt oncogenic Rho signaling in cancer cells with therapeutic implications. Highlights: Uncontrolled activation of Rho signaling by AKAP13 RhoGEF is tumorigenic A hot region for RhoA recognition and activation by AKAP13 was identified Virtual screening discovered an inhibitor of AKAP13-RhoA interaction The compound inhibits oncogenic AKAP13 signals and reverses cancer cell phenotypes Abstract : Diviani et al. found a "hot" region for RhoA recognition and activation by Lbc. Virtual screening of compounds targeting that region discovered an inhibitor of Lbc-RhoA interaction able to halt oncogenic Lbc signals and reverse cancer cell phenotypes.